A Solid Transformation into Carboxyl Dimers Based on a Robust Hydrogen‐Bonded Organic Framework for Propyne/Propylene Separation. Issue 49 (27th October 2021) - Yu, Baoqiu; Geng, Shubo; Wang, Hailong; Zhou, Wei; Zhang, Zhenjie; Chen, Banglin; Jiang, Jianzhuang
Abstract: Self‐assembly of N, N, N ′, N ′‐tetrakis(4‐carboxyphenyl)‐1, 4‐phenylenediamine with the help of different solvents provides isostructural hydrogen‐bonded organic frameworks (HOF‐30). Single‐crystal X‐ray diffraction (SCXRD) analysis reveals HOF‐30 possesses 3D ten‐fold interpenetrated dia nets connected by two kinds of hydrogen bonds, namely solvent‐bridged carboxyl dimers and carboxyl⋅⋅⋅carboxyl dimers. Degassing treatment for HOF‐30 yields HOF‐30a with 3D ten‐fold interpenetrated dia nets but linked with sole carboxyl⋅⋅⋅carboxyl dimers. Reversible hydrogen‐bond‐to‐hydrogen‐bond transformation between solvent‐bridged carboxyl dimers in HOF‐30 and carboxyl⋅⋅⋅carboxyl dimers in HOF‐30a has been unveiled by single‐crystal and powder X‐ray diffraction. In addition, HOF‐30a enables the selective adsorption of propyne over propylene according to single‐component sorption and breakthrough experiments. The preferred propyne location in HOF has also been identified by SCXRD test. Abstract : Reversible solid transformation between solvent‐bridged carboxyl dimers in HOF‐30 and carboxyl⋅⋅⋅carboxyl dimers in HOF‐30a has been unveiled by single‐crystal and powder X‐ray diffraction. In addition, microporous HOF‐30a enables the selective adsorption of propyne over propylene according to single‐component sorption and breakthrough experiments. The preferred propyne location in HOF has also been identified by SCXRD test.